Psihometrične lastnosti slovenskega prevoda lestvice katastrofiziranja bolečine (PCS) - Brečko, Zala (Rehabilitacija (Ljubljana), 2024)
Background: Pain catastrophizing is one of the key psychological constructs that define pain perception, with decatastrophization being one of the primary therapeutic goals enabling more effective coping with the disease for patients. The Pain Catastrophizing Scale (PCS) provides insights into a patient's subjective experience of pain and is useful in clinical practice as a measure of a patient's therapeutic progress regarding pain. In this study, we assessed the psychometric characteristics of the Slovenian version of the PCS scale. Methods: The questionnaire was translated into Slovenian using the standard method and administered to 1756 patients who were evaluated at the Outpatient service for chronic non-malignant pain, University Rehabilitation Institute, Republic of Slovenia, between February 2019 and April 2022. We estimated the reliability and discriminative statistics of items and subscales. To assess the goodness of fit of confirmatory factor analysis models, we used the ?2 test as a measure of statistical fit and five indices as practical fit measures: CFI, TLI, GFI, RMSEA with a 90% confidence interval (CI), and SRMR. Results: Cronbach's alpha coefficient for all 13 items was 0.93, with values of 0.82 for the first factor, 0.78 for the second, and 0.89 for the third. The discriminative index was greater than 0.60 for all items, except for the eighth (0.42). Adequate model fit was confirmed by CFI (0.98), TLI (0.97), GFI (0.99), and RMSEA (0.062; 90% CI). Inadequate model fit was indicated by the statistically significant ?2 value and the SRMR value (0.12). Conclusions: The measurement characteristics of the Slovenian version of the questionnaire are appropriate and comparable to the characteristics of the original: the questionnaire is highly internally reliable, has adequate item discriminative power, and exhibits the anticipated three-factor structure.
Keywords: Chronic Pain; dicriminativeness; diskriminativnost; katastrofiziranje bolečine; kronična bolečina; pain catastrophizing adaptation; priredba; rehabilitation; reliability; Weights and Measures; zanesljivost